2022
DOI: 10.37349/emed.2022.00074
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress in obesity and insulin resistance

Abstract: Since obesity is one of the main factors in the development of insulin resistance (IR) and is also associated with increased oxidative stress (OxS) rate, this study aims to review the published literature to collate and provide a comprehensive summary of the studies related to the status of the OxS in the pathogenesis of obesity and related IR. OxS represents an imbalance between the production of reactive oxygen and nitrogen species (RONS) and the capacity of the antioxidant defense system (AOS) to neutraliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 99 publications
0
23
0
Order By: Relevance
“…Obesity, a state of low-grade systemic in ammation, is associated with ROS overproduction and oxidative stress due to mitochondrial dysfunction (22). As a result, in ammation and oxidative stress are involved in the induction of ER stress signaling pathways and subsequent unfolded protein response (UPR) activation to restore ER homeostasis (23).…”
Section: Discussionmentioning
confidence: 99%
“…Obesity, a state of low-grade systemic in ammation, is associated with ROS overproduction and oxidative stress due to mitochondrial dysfunction (22). As a result, in ammation and oxidative stress are involved in the induction of ER stress signaling pathways and subsequent unfolded protein response (UPR) activation to restore ER homeostasis (23).…”
Section: Discussionmentioning
confidence: 99%
“…Obesity in addition to being the foremost risk factor for T2DM, cardiovascular disease, fatty liver, and hypertension all of which have insulin resistance as the common underlying mechanism; has also been linked to an increased oxidative stress [108]. Obesity is a syndrome of overnutrition and substrate excess leading to glucotoxicity and lipotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Reports showed that leptin and insulin resistance play a vital role in the development of obesity [ 34 , 35 , 36 ]. Additionally, there was a strong positive correlation among insulin resistance, oxidative stress and inflammation [ 37 , 38 ]. Dietary tannic acid, as an antioxidant, effectively improved the liver oxidative damage caused by a high-fat diet ( Figure 3 A).…”
Section: Discussionmentioning
confidence: 99%